Redescription and reevaluation of the extinction risk of Plinia renatiana (Myrtaceae), a species endemic to the state of Espírito Santo, Brazil - Da Fonseca, Heitor Lisboa; Carlos Tuler, Amélia; Da Rosa, Patricia; Freitas, Joelcio; de Lírio, Elton John (Phytotaxa, 2024)
Plinia renatiana is a species endemic to the state of Espírito Santo (ES) and has been assessed as endangered (EN). The species was described in the 1990s based on two samples from the municipality of Linhares. Subsequently, other materials were identified as belonging to the species. However, this set of materials exhibits heterogeneous morphology, which raises doubts about the correct name application. Therefore, it was necessary to expand the species description by incorporating new field-collected data and analyzing a greater number of herbarium specimens. In this study, we analyzed materials deposited in herbaria identified as P. renatiana, reviewed the literature, and conducted field surveys. Based on the collected data, we have expanded the morphological description and reassessed its extinction risk. In addition to the morphological description, taxonomic comments, phenology, a distribution map, and illustrations are provided. In our reassessment, the species was categorized as EN (A2c; B1(i,iii,v) + 2ab(ii,iii,v)), with changes to the criteria used in the 2012 assessment. Despite the review and inclusion of new data, the species has remained in the same threat category in which it was assessed more than a decade ago, underscoring the need for conservation efforts.